Association Between Healthcare-Associated Infection and Exposure to Hospital Roommates and Previous Bed Occupants with the Same Organism. (28th February 2018) - Cohen, Bevin; Liu, Jianfang; Cohen, Adam Ross; Larson, Elaine
Abstract : OBJECTIVE: To quantify the association between having a prior bed occupant or roommate with a positive blood, respiratory, urine, or wound culture and subsequent infection with the same organism. DESIGN: Case-control study. SETTING: The study included 4 hospitals within an academically affiliated network in New York City, including a community hospital (221 beds), a pediatric acute-care hospital (283 beds), an adult tertiary-/quaternary-care hospital (647 beds), and a pediatric and adult tertiary-/quaternary-care hospital (914 beds). PATIENTS: All 761, 426 inpatients discharged from 2006 to 2012 were eligible. Cases included all patients who developed a healthcare-associated infection (HAI) with Staphylococcus aureus, Acinetobacter baumannii, Streptococcus pneumoniae, Pseudomonas aeruginosa, Klebsiella pneumoniae, Enterococcus faecalis, or Enterococcus faecium . Controls were uninfected patients matched by fiscal quarter, hospital, and length of stay. For each bed occupied during the 3–5-day period prior to infection, microbiology results for assigned roommates and the patient who occupied the bed immediately prior to the case were collected. For controls, the day of infection of the matched case served as the reference point. RESULTS: In total, 10, 289 HAIs were identified. In a multivariable analysis controlling for both exposures and patient characteristics, the odds of cases having been exposed to a prior bed occupant with the same organism were 5.83 times that of controls (95% confidence interval [CI], 3.62–9.39), and the odds of cases having been exposed to a roommate with the same organism were 4.82 times that of controls (95% CI, 3.67–6.34). CONCLUSION: Infected or colonized roommates and prior occupants do pose a risk, which may warrant enhanced terminal and intermittent cleaning measures. Infect Control Hosp Epidemiol 2018;39:541–546